Impact of internal remittance on households' use of bank services: evidence from Vietnam - Nguyen, Thu Thi Hoai (2022)
Purpose: This study estimates impact of remittances from internal migration on households' use of bank services in Vietnam. Design/methodology/approach: This study uses data from the Vietnam Household Living Standards Survey and the two-stage least squares method (2SLS). Findings: The results show that receiving internal remittance increases households' probability of having bank accounts and using card services. However, these impacts are different between rural and urban areas. Research limitations/implications: The results of this study reveal the useful role of internal remittance in increasing the probability of households using bank services, thereby enhancing financial inclusion in Vietnam. Originality/value: Different from the previous studies, the purpose of this paper is to analyse the impact of internal remittance on the use of bank services in Vietnam at the household level. This paper targets internal migration because it is the main type of migration in Vietnam. Besides, to the best of the authors’ knowledge, this research is the first one that compares the role of internal remittance on households' use of bank services in rural and urban areas in Vietnam.